Bakhtin and Multicuturalism-Bakhtin revisited in Paoulo Coehlo - Anjum, Rehana Yasmin (Advances in Social Sciences Research Journal, 2016)
Mikhail Bakhtin(1895-1975),a Russian philosopher, thinker and above all a discourse theorist with his own linguistic philosophy was brought into the limelight in 1960s from the attic memory is considered to be a stir in the town. Bakhtinian philosophy of language can be defined in terms of his concepts about linguistic ability. His dialogism. a specie specific(‘human not atomized’), considered to be a continuous dialogue(‘dialogism’)that is ever going never finalized(‘unfinalizable’),created(‘creative’),developed(‘action and response’), evolved(‘evolution’) in a context(‘social phenomenon’), bounded by a spatio-temporal frame(‘chronotopes’) between interlocutors(‘I’, ‘me’,’other’,and ‘others’) generates response in the listener by motivating the others to reflect their thoughts in the form of a live event(‘heteroglossia’-‘polyphony’ The pivotal feature of this polyphony is the independence of different voices giving individuality to an expression. Paulo Coelho born in 1947 at Brazil as a ‘dead boy’ brought Bakhtin’s dialogics in action in its fullest. He spent his early life in Brazil as a warrior’s l while struggling for survival. This was this struggle that equates him with Bakhtin who was also an epitome of resistance against odds both physical and social . Multiculturalism in a broader sense is an amalgamation of different cultures where each allows the other a space for self expression as well as respect to preserve the identity of their community or nation on their own terms. The present study has compared both philosophers on thematic level to show that a multicultural society is the solution of today’s extremism in attitudes on global level. The sample taken for comparison of themes is one novel ‘The Zahir’ of Coelho. It reflects some of the major themes of the writer which are in the same vein of the philosophical genius of Bakhtin.